MENINGKATKAN LITERASI PAJAK WPOP MELALUI ASISTENSI PENGISIAN SPT E-FILING - Fenny, Tara Aurellia; Lukman, Hendro (Jurnal Serina Abdimas, 2024)
Community Service through Tax Volunteer activities carried out by these students focuses on increasing knowledge through assistance to Individual Taxpayers (WPOP) in reporting Annual Tax Returns (SPT) by e-filing. This literacy activity through SPT reporting assistance aims to ensure that taxpayers report carrying out their tax obligations correctly. This activity was carried out at the Kalderes Tax Service Office during March 2024. Literacy was provided at the same time as filling in the WPOP's Annual Tax Return face to face and guiding WPOP to fill in their tax information in the e-filing system. This activity hopes that WPOP will gain knowledge and skills on how to fill out SPT by e-filing so that next year they can fill it in correctly themselves so that filling in SPT is more efficient and increases the ratio of WPOP reporting SPT. From the results of the activity, it is hoped that the activities of Tax Volunteers who carry out PKM activities through assistance in filling out SPT with e-Filing can be an effective strategy in increasing tax literacy and tax compliance in Indonesia. ABSTRAK Pengabdian Kepada Masyarakat melalui kegiatan Relawan Pajak yang dilakukan oleh para mahasiswa ini berfokus untuk meningkatkan pengetahuan melalui asistensi kepada Wajib Pajak Orang Pribadi (WPOP) dalam pelaporan Surat Pemberitahuan Tahunan (SPT) dengan e-filing. Kegiatan literasi melalui asistensi laporan SPT ini bertujuan agar WPOP melaporkan melakukan kewajiban perpajakannya dengan benar. Kegiatan ini dilakukan di Kantor Pelayanan Pajak Kalideres selama bulan Maret 2024. Literasi yang diberikan bersamaan pengisian Annual Tax Return WPOP secara tatap muka dan membimbing WPOP mengisi informasi pajaknya pada sistem e-filing. Kegiatan ini diharapkan WPOP mendapat pengetahuan dan ketrampilan bagaimana mengisi SPT dengan e-filing sehingga tahun berikutnya mereka dapat mengisi sendiri dengan benar sehingga pengisian SPT lebih efisien dan meningkatkan rasio WPOP yang melaporkan SPT. Dari hasil kegiatan, diharapkan kegiatan Relawan Pajak yang melakukan kegaitan PKM melalui asistensi pengisian SPT dengan e-Filing dapat menjadi strategi efektif dalam meningkatkan literasi pajak dan kepatuhan pajak di Indonesia.